Effect of isometric quadriceps in reduce pain in patients of knee osteoarthritis - Warsono, Warsono; Rachmawati, Anita; Fahmi, Faradisa Yuanita (University of Muhammadiyah Semarang, 2021)
Osteoarthritis (OA) is a degenerative disease that often occurs, both in Indonesia and abroad. OA is characterized by progressive destruction of joint cartilage and causes structural changes in the joints. OA disease from grades 1 to 4 has symptoms that are usually difficult for the sufferer's life. One of these symptoms is joint pain, but reducing pain intensity, especially OA grades 1 to 3, it can be done with exercise. The use of this exercise is an isometric quadriceps exercise. The design of this study used a quasi-experimental design with a pre-post test control group design with a sample of 40 respondents who met the inclusion and exclusion criteria, namely patients with knee osteoarthritis, stage II, and III who underwent the initial rehabilitation program. Based on the results of data processing using the Wilcoxon test in the control group, the p-value = 0.01 < 0.05, while in the intervention group the p-value = 0.00 < 0.05. From these results, it can be concluded that isometric quadricep exercise is effective in reducing pain intensity in osteoarthritis genu grades 1 to 3. So isometric quadricep exercise can be recommended as an independent therapy in reducing knee osteoarthritis pain intensity.